Pengaruh Jenis Residu Kompos Biochar dan Umur Defoliasi Daun Jagung (Zea mays L.) terhadap Pertumbuhan dan Hasil Kacang Merah (Phaseulus vulgaris L.) dalam Tumpangsari Salome - Krisantus Tri Pambudi Raharjo; Venidora R. Delang (Fakultas Pertanian, Universitas Timor, 2020)
This study aims to determine the effect of residues of biochar compost in the second crop season and the effect of defoliation age treatment on corn leaves on growth and yield of red bean plants with corn salome intercropping. The research was carried out from July to November 2019 in the experimental garden of the Faculty of Agriculture, University of Timor, Sasi Village, Kota Kefamenanu District, TimorTengah Utara Regency (TTU), Nusa Tenggara Timur Province (NTT). This study used a factorial 3 x 3 Randomized Block Design (RAK) which was repeated 3 times. The first factor is the type of biochar residue which consists of 3 levels, namely cow manure biochar compost residue, goat manure biochar compost residue, horse manure biochar compost residue. The second factor was the time of defoliation of corn leaves which consisted of 3 levels, namely without defoliation, defoliation at 35 DAP, defoliation at 55 DAP, so there were 9 treatment combinations, which were repeated 3 times so that there were 27 experimental units. The results showed that there was a positive effect according to the DMRT test at 5% level between the combination of biochar compost residue treatment and corn leaf defoliation age treatment on soil temperature 60 DAP, soil volume weight 60 DAP, and canopy dry weight. The single factor treatment of biochar compost residue enriched with goat manure was able to modify the plant growing environment and increase plant growth and yield. The single factor treatment of corn leaf defoliation age 35 DAP was able to increase the growth and yield of red bean plants.